‘Sana All’: The Occurrence of Envy on Facebook Use and Its Correlation to Self-Esteem among Philipphine Young Adults - Aira Juliana Baltazar (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
The present study explore the association between facebook use, envy, social comparison and self-esteem using a quantitative correlational descriptive design. Participants in this research were young adult in Philiphine aged 18-24 years-old, as this is the age group most engaged on Facebook. Data were collected using questionnaires. The data analysis indicated that respondents spent an average of 3-4 hours every day on Facebook. Meanwhile, the type of envy they most commonly express was benign envy rather than malicious envy. This finding demonstrates that when these people encounter anything that stimulates their feelings of envy, they seek to improve their situation rather than criticizing the people they envy. However, the findings of this study do not support the hypothesis that there is a significant relationship between the occurrence of different types of envy and self-esteem. As a result, the findings may indicate a variety of explanations for why the study produced these results which was explained in this paper.